Pemeriksaan Dan Pemantauan Kesehatan Gigi Dan Mulut Pada Anak Usia Dini Di TK Terpadu Alif Center Kabupaten Jombang - Mudhawaroh Mudhawaroh; Niken Grah Prihartanti; Septi Fitrah Ningtyas; Rosa Purwanti (PEKAT: Jurnal Pengabdian Kepada Masyarakat, 2023)
Health is highly essential, especially when it comes to issues with dental and oral health. Early dental and oral health care is important so that children develop the behaviors necessary to maintain cleanliness and good oral and dental health. In addition to assessing the children's oral and dental hygiene, this community activity strives to educate the public on the need of maintaining good dental and oral health. Based on community service findings, it was discovered that as many as 9 children (39%) had clean teeth and mouths. With this activity, it is intended that children may use the proper technique for brushing their teeth and can always improve oral and dental health. Additionally, it is intended that the school will be able to monitor kids thoroughly so that it can ensure their general wellbeing. Keywords: Early childhood, Dental and oral health examination and monitoring.